Effect of an online healthy lifestyle psychoeducation programme to improve cardiometabolic outcomes and affective symptoms in youth receiving mental health care: study protocol for a pilot clinical trial. - Elizabeth M Scott; Ian B Hickie; Chloe Wilson; Alissa Nichles; Natalia Zmicerevska; Yun Ju Christine Song; Joanne Sarah Carpenter; Blake Hamilton; Catherine McHugh; Samuel Hockey (BMJ Open)
Introduction Worsened cardiometabolic profiles in youth with mental ill health have been associated with a number of modifiable lifestyle risk factors. It is becoming increasingly evident that clinical interventions need to be multimodal in focus to improve mental health symptoms and the physical health symptoms in this already at-risk cohort.Methods and analysis This 12-week pilot clinical trial examines the efficacy, feasibility and acceptability of an adjunctive online psychoeducation programme for improving cardiometabolic risk parameters and affective symptoms in a transdiagnostic sample of at least 44 young people aged 16–25 years presenting for mental healthcare for mood and/or psychotic syndromes (including anxiety, depression, bipolar disorder and psychosis). Individuals will be invited to participate in a pilot clinical trial for a structured online psychoeducation programme incorporating nutritional, physical activity, sleep–wake and healthy lifestyle information, delivered fortnightly over six online modules. Participants will undergo a series of assessments including: (1) self-report and clinician administered assessments determining mental health symptomatology; (2) fasting blood tests to assess cardiometabolic markers (fasting insulin, fasting glucose and blood lipids); (3) anthropometric assessments (height, weight, waist circumference and blood pressure); and (4) sleep–wake behaviours and circadian rhythm assessments. Changes in scores for all cardiometabolic and affective measures will be assessed via paired samples t-tests, and correlations between change scores will be assessed via Pearson’s or Spearman’s correlations. Feasibility will be assessed via completion rates, and the acceptability of the programme will be assessed via programme satisfaction measures.Ethics and dissemination This pilot clinical trial has been approved by the Sydney Local Health District Research Ethics and Governance Office (X20-0228 & 2020/ETH01201). The results of this pilot clinical trial will be disseminated into the scientific and broader community through peer-reviewed journals, conference presentations, social media and university websites.Trial registration number Australian New Zealand Clinical Trials Registry (ANZCTR) Number: ACTRN12620000772943, Date 28 August 2020.